The changes of tumour vascular endothelial growth factor expression after neoadjuvant chemoradiation in patients with rectal adenocarcinoma - Buka, David; Dvorak, Josef; Sitorova, Veronika; Sirak, Igor; Voboril, Rene; Melichar, Bohuslav; Richter, Igor (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : The aim was to examine the effects of neoadjuvant chemoradiotherapy on VEGF expression in patients with locally advanced rectal cancer. Materials and methods : A total of 53 patients with locally advanced rectal cancer were retrospectively studied. Neoadjuvant treatment comprised external beam radiation (50.4 Gy/28 fractions) with continuous infusion of 5-fluorouracil. Four to 6 weeks after the chemoradiotherapy, the patients underwent surgical resection. Immunohistochemistry was performed to assess VEGF expression in the pretreatment biopsies and in resected specimens. Results : Resection with microscopic residual tumour (R1) was performed in two patients while in the remaining 51 patients radical resection with microscopically negative margins (R0) was possible. Downstaging after preoperative chemoradiotherapy was observed in 34 patients (64%). After chemoradiotherapy 24 patients (45%) had decreased VEGF expression, in 20 patients (38%) there was no change, and in two patients it was not possible to assess the dynamics of VEGF expression due to pathologic complete response after chemoradiotherapy. The five-year overall survival (OS) rate was 56% (95% CI: 43–70%). Although the median OS was 2.5 times shorter in patients who experienced decreased VEGF expression during therapy, this difference did not reach statistical significance. VEGF expression was not significant in Cox regression analysis or log-rank test. VEGF expression decreased after neoadjuvant chemoradiotherapy in most patients with rectal adenocarcinoma examined. This decrease was associated with a trend of inferior prognosis. Conclusions : VEGF expression decreased after neoadjuvant chemoradiotherapy in most patients examined. This decrease was associated with a trend of inferior prognosis.